Peer Tutoring with QUICK Method vs. Task Based Method on Reading Comprehension Achievement - Indrawati, Sri (Beyond Words, 2017)
This study is a quasi-experimental research analyzing the reading comprehension achievement of the eleventh graders of Senior High School in Surabaya. This experimental research is comparing the effects of peer tutoring with QUICK method and task-based method to help the students to increase the students’ reading achievement. Besides for increasing the students’ reading achievement, this study has the main purpose to give a variation in teacher’s teaching reading techniques. This study uses independent samples t-test and paired samples t-test to indicate the students’ significant difference in achieving the reading comprehension in peer tutoring with QUICK method and task based method. Keywords: Peer tutoring with QUICK method, Task-based method, T-test, Reading achievement